Is Boreout a Threat to Frontline Employees' Innovative Work Behavior?1. Issue 4 (8th October 2014) - Stock, Ruth Maria
<x xml:space="preserve">Abstract</x> With the recognition that innovation is the lifeblood of competitive firms, researchers have investigated multiple antecedents of employees' innovative work behaviors. Most studies focus on supportive work conditions, work requirements, or even high work challenges as drivers of innovative work behavior as the extent to which frontline employees (FLEs) generate new problem‐solving ideas and transform these into uses during the service encounter. This study focuses instead on a lack of resources at the service encounter. Specifically, boreout is a negative psychological state of low work‐related arousal, manifested in three main forms: a crisis of meaning at work, job boredom, and crisis of growth. According to the conservation of resources theory, these three dimensions of job boreout as lack of resources draw energy from FLEs and thus, likely affect innovative work behavior. Data from 142 FLEs and their customers confirm that these dimensions of boreout affect FLEs' innovative work behavior, though in varying ways. A crisis of meaning at work and crisis of growth both impede innovative work behavior, but job boredom has no effect. Furthermore, support provided by customers moderates the relationships of these three boreout dimensions with innovative work behavior in unique ways.